Role of Microfinance for Poverty Reduction and Women Empowerment - Pokharel, Ram Raj (Patan Prospective Journal, 2022)
Microfinance is a financial and social intermediation to the poor or especially for women. Microfinance provides financial services like micro credit, micro saving, micro insurance and micro remittance. Easy services of microfinance attracted back ward women, which may be caused to push women toward new horizon. In this article, the researcher has defined the new horizon as empowerment of women. Empowerment is a situation where women have their self-dependency, free mobility, free participation on their own desired sector and field. The meaning of empowerment becomes meaning-full when women become economically, socially and politically strong. In this regard, this study aims to explore to identify the role of microfinance has played to poverty reduction and to find out role of microfinance to women empowerment. The study has been based on primary source, data collected from interview schedule by fulfilling the validity from the review of literature with the sample from Mahila Sahayogi Sahakari Bachat Tatha Rin Sahakari Sanstha, Tarakeswar Municipality ward no. 2. The sample includes 60 respondents. The study concludes that the there is a improvement in the earnings and stimulated the living standard of women beneficiaries from the microfinance The study further concludes the member of microfinance women of the study area are becoming active mentally and physically as the way their participation, communication, fund management discussion, cooperative power and accountability.